Analysis of the Human Body's Resistance to AC Voltage - Billy Kilis; Maickel Tuegeh; Rahmat Dako; Viverdy Memah; Janne Ticoh (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2023)
The economic development of the community affects the widespread use of household electricity. Of course, the development of technology touches every aspect of the activity, whether for entertainment, pleasure or primary needs. Every dry season, the threat of fire is often a scourge for all of us. One of the leading causes is a short circuit of electric current. Electricity is an essential part of this day and age. Everyone needs electricity, whether it is from the lower levels of society to the upper levels of society, both for household, office and industrial purposes. Specifically for household purposes, electricity has become an inseparable part of daily needs. A pandemic has resulted in more extended and varied use of electricity in the home. Another consequence is that it is more prone to short circuits or even fires. The critical criteria that must be met at home are the proper installation of security fuses, the avoidance of sockets with multiple connections, and other items that must guarantee adequate grounding or fulfil the requirements with installations that meet the General Electrical Installation Requirements (in Bahasa Indonesia is abbreviated as PUIL). Problems that can be identified are: What is the average resistance of the student body to AC voltage? Are there any differences in male and female body resistance? The benefits of this research are: Theoretical benefits assessing the average resistance of the human body for planning protection system equipment. Practical benefits it is known as the average student body resistance value. Become a reference in determining the value of a protection system plan. The average measurement results in the range of 5100 Ohm. The results showed a significant difference between the levels of body resistance of male and female students. This is because the number of female students in this study is much smaller than that of male students.